Emotional Intelligence, Leadership Effectiveness, and Team Performance: Synergies in Human Resource Development - Antariksa, Sri Kartika Sari (Penerbit Goodwood, 2025)
Purpose: This study explores how emotional intelligence (EI) influences leadership effectiveness and team performance. It identifies key EI components that drive effective leadership behaviors and examines their impact on team dynamics. Additionally, the study provides insights for human resource practitioners on incorporating EI into leadership development programs to foster cohesive and high-performing teams. Methodology: This research adopts a qualitative approach, utilizing a literature review and library research. It examines scholarly articles, books, and empirical studies related to emotional intelligence, leadership effectiveness, and team performance. Various emotional intelligence models and leadership styles are analyzed to understand their influence on team outcomes. Results: The findings indicate a strong correlation between emotional intelligence and leadership effectiveness. Leaders with high EI are more capable of fostering trust, encouraging open communication, and managing team conflicts—all of which enhance team performance. Traits such as empathy, self-awareness, and social skills are identified as crucial in promoting team cohesion and productivity. Conclusions: Emotional intelligence, leadership effectiveness, and team performance are essential components of high-performing organizations. Emotionally intelligent leaders cultivate trust, collaboration, and motivation, resulting in improved outcomes. Integrating emotional intelligence into leadership training significantly enhances both individual and team success. Limitations: The interviews conducted through questionnaires may lack validity, as the responses could not be directly verified. Additionally, the questionnaire items were derived from limited sources, which may have affected the reliability of the results. Contribution: This research is expected to enhance organizational and team performance and serve as a reference model for future studies.